2011
DOI: 10.1111/j.1467-7652.2011.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Wheat streak mosaic virus generated by expression of an artificial polycistronic microRNA in wheat

Abstract: SummaryWheat streak mosaic virus (WSMV) is a persistent threat to wheat production, necessitating novel approaches for protection. We developed an artificial miRNA strategy against WSMV, incorporating five amiRNAs within one polycistronic amiRNA precursor. Using miRNA sequence and folding rules, we chose five amiRNAs targeting conserved regions of WSMV but avoiding off-targets in wheat. These replaced the natural miRNA in each of five arms of the polycistronic rice miR395, producing amiRNA precursor, FanGuard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 62 publications
1
81
0
Order By: Relevance
“…Another fundamental aspect of artificial miRNA is that it has been used to downregulate the expression of exogenous genes e.g., the invading virus pathogen in wheat, such as the wheat streak mosaic virus (Fahim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Another fundamental aspect of artificial miRNA is that it has been used to downregulate the expression of exogenous genes e.g., the invading virus pathogen in wheat, such as the wheat streak mosaic virus (Fahim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed several studies demonstrated that artificial miRNAs (amiRNAs) targeting key components of the viral replication machinery can efficiently impair viral growth upon infection [59][60][61][62][63][64][65]. These efforts have revealed that such resistance is cell-autonomous, inheritable, more efficient than siRNA-mediated strategies and successful in blocking viral replication and movement [59,66].…”
Section: Sncrnas and Viruses: New Frontiers Of Defensementioning
confidence: 99%
“…These efforts have revealed that such resistance is cell-autonomous, inheritable, more efficient than siRNA-mediated strategies and successful in blocking viral replication and movement [59,66]. Furthermore transgenic plants expressing dimeric or polycistronic amiRNAs directed against different viruses result in a wider spectrum of viral resistance [60,61,63].…”
Section: Sncrnas and Viruses: New Frontiers Of Defensementioning
confidence: 99%
“…A major limitation of the amiRNA strategy is that the small size of the amiRNA (21nt) increases opportunities for loss of complementarity between the amiRNA and the target gene, and genes from the same family with variations may not be silenced using a single amiRNA. To reduce these risks, a multimeric amiRNA approach in which multiple amiRNAs targeting different conserved regions of the gene can be adopted as has been reported in plant virus control [69,70].…”
Section: Small Rna (Srna)-mediated Silencingmentioning
confidence: 99%